Modification of the existing maximum residue level for metalaxyl‐M in honey - European Food Safety Authority (EFSA); G. Bellisai; G. Bernasconi; L. Carrasco Cabrera; I. Castellan; M. delAguila; L. Ferreira; L. Greco; S. Jarrah; R. Leuschner; A. Mioč; S. Nave; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Ascenza Agro S.A. submitted a request to the competent national authority in France to modify the existing maximum residue level (MRL) for the active substance metalaxyl‐M in honey. The data submitted in support of the request were found to be sufficient to derive MRL proposal for honey. Adequate analytical methods for enforcement are available to control the residues of metalaxyl‐M in honey matrix at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues expected in honey resulting from the existing uses of metalaxyl‐M on melliferous crops reported by the Applicant is unlikely to present a risk to consumer health.